2001
DOI: 10.1186/rr42
|View full text |Cite
|
Sign up to set email alerts
|

Th2 cytokines and asthma — Interleukin-9 as a therapeutic target for asthma

Abstract: Asthma is a complex heritable inflammatory disorder of the airways in which the development of clinical disease depends on environmental exposure. It has been well established that T helper type 2 (T H 2) lymphocytes and their cytokines have an important role in allergic asthma. Interleukin (IL)-9, a member of the T H 2 cytokine family, has recently been implicated as an essential factor in determining mucosal immunity and susceptibility to atopic asthma. In this review we examine the critical experiments and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(10 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…Additionally, IL-9 was termed a candidate gene for asthma since it was found by linkage analyses to reside within a cytokine gene cluster together with IL-3, IL-4, and IL-5 on human chromosome 5 (8). In line with these findings, IL-9 as a pleiotropic cytokine, has several activities that favor the development of allergic asthma (9, 10). IL-9 enhances the IL-4-mediated production of IgE in human and murine B cells (11), promotes eosinophil maturation in synergy with IL-5 (12), and stimulates mucin transcription in respiratory epithelial cells (13).…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…Additionally, IL-9 was termed a candidate gene for asthma since it was found by linkage analyses to reside within a cytokine gene cluster together with IL-3, IL-4, and IL-5 on human chromosome 5 (8). In line with these findings, IL-9 as a pleiotropic cytokine, has several activities that favor the development of allergic asthma (9, 10). IL-9 enhances the IL-4-mediated production of IgE in human and murine B cells (11), promotes eosinophil maturation in synergy with IL-5 (12), and stimulates mucin transcription in respiratory epithelial cells (13).…”
Section: Introductionsupporting
confidence: 52%
“…IL-9 was initially thought to be preferentially produced by Th2 cells and subsequently it has been shown that IL-9 induced asthmatic symptoms similar to those induced by IL-4 (9, 10). This asthma-promoting potency of IL-9 was found to be at least partially mediated by IL-13 that was produced from airway epithelial cells (36).…”
Section: Discussionmentioning
confidence: 99%
“…Transgene expression of IL-9 in the lungs of mice resulted in lymphocytic and eosinophilic infiltration of the lung, airway epithelial hypertrophy with mucus production, mast cell hyperplasia and production of IL-4, IL-5 and IL-13 [53]. Blocking humanized antibodies to IL-9 are currently in development [54]. However, these may also prove to be disappointing, as the overall current evidence does seem to suggest that targeting single T cell cytokines would not be an effective therapeutic approach for asthma.…”
Section: Eosinophil Accumulation -Il-4 and Il-13mentioning
confidence: 98%
“…Transgene expression of IL-9 in the lungs of mice resulted in lymphocytic and eosinophilic infiltration of the lung, airway epithelial hypertrophy with mucus production, mast cell hyperplasia and production of IL-4, IL-5 and IL-13 [45]. Blocking humanised antibodies to IL-9 are currently in development [46]. TNF-α is expressed in asthmatic airways and levels are elevated in induced sputum from patients with COPD [47].…”
Section: Pro-inflammatory Cytokinesmentioning
confidence: 99%